Reducing operational time complexity of k-NN algorithms using clustering in wrist-activity recognition - Choe, Sun Taag; Cho, We Duke; Kim, Jai Hoon; Kim, Ki Hyung (Intelligent Automation and Soft Computing, 2020)
Recent research on activity recognition in wearable devices has identified a key challenge: k-nearest neighbors (k-NN) algorithms have a high operational time complexity. Thus, these algorithms are difficult to utilize in embedded wearable devices. Herein, we propose a method for reducing this complexity. We apply a clustering algorithm for learning data and assign labels to each cluster according to the maximum likelihood. Experimental results show that the proposed method achieves effective operational levels for implementation in embedded devices; however, the accuracy is slightly lower than that of a traditional k-NN algorithm. Additionally, our method provides the advantage of controlling the computational burden, depending on the performance of the embedded device on which the algorithm is implemented.
Keywords: Embedded wearable device; Human-activity recognition; Instance reduction; K-means clustering; K-nearest neighbors; Triaxial signal